Probing the CMB cold spot through local Minkowski functionals - Zhao, Wen (Research in astronomy and astrophysics, 2014)
Both the Wilkinson Microwave Anisotropy Probe （WMAP） and Planck missions have reported an extremely cold spot （CS） centered at Galactic coordinate （1 = 209°, b = -57°） in the cosmic microwave background map. We study the lo- cal non-Gaussianity of the CS by defining local Minkowski functionals. We find that the third Minkowski functional v2 is quite sensitive to the non-Gaussianity caused by the CS. Compared with random Gaussian simulations, the WMAP CS deviates from Gaussianity at more than a 99% confidence level with a scale of R - 10°. Meanwhile, we find that cosmic texture provides an excellent explanation for these anomalies re- lated to the WMAP CS, which could be further tested by future polarization data.